Los derechos de la naturaleza y el derecho de las personas a beneficiarse de las riquezas naturales - Albán Ortiz, Pablo Andrés (2024)
This study analyzes the scope of the guarantee of the rights of nature and of people to benefit from it in harmony, for their well-being. It was based on the analysis of previous investigations, constitutional regulations, secondary legislation, and jurisprudence of the Constitutional Court. The general objective was to determine the scope of the rights of nature and the rights of people to benefit from it in harmonious coexistence, through the analysis, assessment and weighting of administrative decisions or judicial cases in which negative environmental or social consequences have been detected. due to excesses in the exercise of rights. Its importance lies in establishing that these rights are not opposite or contradictory but rather interdependent and that human coexistence with nature in harmony is possible. The research had a qualitative approach, documentary type and level of explanatory depth. The methods used were normativism and inductive. Documentary and interview techniques were applied. The results indicate that the rights of nature and of people to benefit from its riches for their subsistence are not exclusive, but interdependent\; when man and nature integrate these ecosystems and coexist in harmony by having developed ancestral practices in their relationship with nature, respecting their life cycles, the balance of ecosystems, and their capacity for regeneration. The survival of humanity depends on the conservation of nature. On the other hand, there is permanent tension between the rights of nature and article 74 of the Constitution, when the holders of environmental licenses cause negative impacts to nature, illegal activities of extraction of non-renewable resources that depredate it\; and, the National Environmental Authority, in cases in which by action, omission or inappropriate decisions it fails to fulfill its own powers by not exercising control, monitoring, surveillance and intervention to the operators, to protect and guarantee the rights of nature.